Effect of 3 and 6 mg/kg of caffeine on fat oxidation during exercise in healthy active women - Varillas-Delgado, David; Aguilar-Navarro, Millán; Muñoz, Alejandro; López-Samanés, Álvaro; Ruiz-Moreno, Carlos; Posada-Ayala, María; Amaro-Gahete, Francisco J.; Coso, Juan; Gutiérrez-Hellín, Jorge (Biology of Sport, 2023)
The aim of this study was to investigate the effect of 3 and 6 mg of caffeine per kg of body mass (mg/kg) on whole-body substrate oxidation during an incremental cycling exercise test in healthy active women. Using a double-blind placebo-controlled counterbalanced experimental design, 14 subjects performed three identical exercise trials after the ingestion of 3 or 6 mg/kg of caffeine or placebo. The exercise trials consisted of an incremental test on a cycle ergometer with 3-min stages at workloads from 30 to 70% of maximal oxygen uptake (VO2max). Substrate oxidation rates were measured by indirect calorimetry. During exercise, there was a significant effect of substance (F = 5.221; p = 0.016) on fat oxidation rate. In comparison to the placebo, 3 mg/kg of caffeine increased fat oxidation rates at 30 to 60% of VO2max (all p < 0.050) and 6 mg/kg at 30 to 50% of VO2max (all p < 0.050). There was also a significant effect of substance (F = 5.221; p = 0.016) on carbohydrate oxidation rate (F = 9.632; p < 0.001). In comparison to placebo, both caffeine doses decreased carbohydrate oxidation rates at 40 to 60% VO2max (all p < 0.050). The maximal rate of fat oxidation with placebo was 0.24±0.03 g/min, which increased with 3 mg/kg to 0.29±0.04 g/min (p = 0.032) and to 0.29±0.03 with 6 mg/kg of caffeine (p = 0.042). Acute intake of caffeine improves the utilization of fat as a fuel during submaximal aerobic exercise in healthy active women with an effect of similar magnitude after the intake of 3 and 6 mg of caffeine per kg of body mass. Thus, the use of 3 mg/kg of caffeine would be more recommended than 6 mg/kg for women seeking increased fat utilization during submaximal exercise